BACTERIOLOGICAL INVESTIGATION OF PRAWN CANNERIES II. INCIDENCE OF CLOSTRIDIUM PERFRIDGENS - NAMBIAR, V NARAYANAN; IYER, K MAHADEVA (Fishery Technology, 2016)
Prawn processing factories of the three major fish processingcentres of the West Coast of India, viz., Cochin, Mangalore andCalicut were surveyed to determine the occurrence of Clostridiumperfringens in processing areas, and in processed products. Directplating on Sulphite -polymyxin- sulphadiazine Agar and enrichmenttechniques were used. Samples of prawn, prawn guts, frozen prawns,canned prawns, water, ice, swab from utensils and soil from the factorypremises were examined. Among a total of 461 samples examined,only 32 (6.9%) gave positive results. The incidence of C. pe1jringenswas more in prawn guts (80%), followed by soil (50%), prawn (38%),ice (33.3%), frozen prawns (11%), swab (5.0%) and water (1.1%).No C. perfringens was isolated from canned prawns.